Enhancing reading comprehension through schemata / Chai Moo Hung - Chai, Moo Hung (Universiti Teknologi MARA, Pahang, 1990)
How does one read? Reading theorists suggest that there is really more to reading than meets the eye, contrary to the popular belief that reading is a "passive" activity. For complete recovery of the writer's meaning, early reading research saw the reader plodding through a text in the letter-by-letter, word-by-word fashion, and in a precise manner, from print to speech to comprehension. Comprehension was a matching of sounds and letters. If well processed, it led to comprehension (Gough 1972). Implicit in this view of reading is that meaning rests with the print and is the end product of the step-by-step processing of texts.